Pilgrims and Sacred Sites in China - Naquin, Susan; Y|, Ch|n-Fang (Studies on China ;, 2020)
Until now, China has been scarcely represented in the burgeoning comparative literature on pilgrimage. This volume remedies that omission, discussing the interaction between pilgrims and sacred sites from the tenth century to the present. From the perspectives of literature, art, history, religion, politics, and anthropology, the essays focus on China's most famous pilgrimage mountains as well as lesser known sites.